2021
DOI: 10.3233/adr-201000
|View full text |Cite
|
Sign up to set email alerts
|

Superior Frontal Gyrus TOMM40-APOE Locus DNA Methylation in Alzheimer’s Disease

Abstract: Background: The APOE ɛ4 allele is the strongest known genetic risk factor for sporadic Alzheimer’s disease (AD). The neighboring TOMM40 gene has also been implicated in AD due to its close proximity to APOE. Objective: Here we tested whether methylation of the TOMM40-APOE locus may influence ApoE protein levels and AD pathology. Methods: DNA methylation levels across the TOMM40-APOE locus and ApoE levels were measured in superior frontal gyrus tissues of 62 human brains genotyped for APOE and scored for AD neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These discrepancies may be due to racial and geographical differences. The two ApoE polymorphisms, rs429358 and rs7412 , are located in the coding region of exon 4, which overlaps with a clearly defined CpG island, distinguishing the three prevalent ApoE alleles, ɛ 2, ɛ 3, and ɛ 4 ( Bezuch et al, 2021 ). Both SNPs alter the number of CpG dinucleotides, which are the main locations for DNA methylation, in addition to the protein codon.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to racial and geographical differences. The two ApoE polymorphisms, rs429358 and rs7412 , are located in the coding region of exon 4, which overlaps with a clearly defined CpG island, distinguishing the three prevalent ApoE alleles, ɛ 2, ɛ 3, and ɛ 4 ( Bezuch et al, 2021 ). Both SNPs alter the number of CpG dinucleotides, which are the main locations for DNA methylation, in addition to the protein codon.…”
Section: Discussionmentioning
confidence: 99%
“…A high-density whole-genome association study showed strong associations between SNPs neighboring the APOE loci and AD risk [ 11 ]. Although APOE is a strong risk factor for AD, it is believed that additional factors with the APOE locus contribute to the pathogenesis of AD [ 18 , 45 , 46 ]. The TOMM40 gene is within APOE -surrounding regions and is located in proximity to the APOE gene [ 18 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although APOE is a strong risk factor for AD, it is believed that additional factors with the APOE locus contribute to the pathogenesis of AD [ 18 , 45 , 46 ]. The TOMM40 gene is within APOE -surrounding regions and is located in proximity to the APOE gene [ 18 , 46 ]. DNA samples from 80 Taiwanese AD patients were examined using a targeted panel of whole-genome sequencing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations